EFEKTIFITAS PENGGUNAAN CAMPURAN AIR PANAS DENGAN JERUK NIPIS (Citrus aurantifolia) DAN AIR PANAS DALAM MENURUNKAN JUMLAH BAKTERI Staphylococcus aureus YANG TERDAPAT PADA PAKAIAN BEKAS PADA PASAR TRADISIONAL PERUMNAS SIMALINGKAR KOTA MEDAN TAHUN 2015 - ririn nainggolan; nurmaini *; indra chahaya (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Bacteria is one of the microorganisms that cause infection. Some species of bacteria are pathogens that cause disease in humans, such as infections caused by Staphylococcus aureus. These bacteria can live on imported used clothing. This research goal is to determine whether or not a decrease in the number of bacteria Staphylococcus aureus in second-hand clothes on the use of a mixture of hot water with lime (Citrus aurantifolia) and the hot water in traditional markets Perumnas Simalingkar. This research is quasi experimental with the design used in this study was conducted with the approach of pre-test and post test which measurements were performed before and after treatment. The study was conducted in September to January 2016. The sample in this study is used clothing sold in traditional markets Perumnas Simalingkar. Data were analyzed descriptively. The results showed that the decrease in the number of Staphylococcus aureus in the control treatment, a mixture of hot water and lime 10%, and the hot water for 10 minutes was 220 CFU / ml, 0 CFU / ml, and 23.3 CFU / ml. Decreasing in the number of bacteria Staphylococcus aureus is most effective in the treatment of mixtures of hot water with lime with a percentage decrease of 100%. Community is suggested that perform the immersion of used clothing before wearing old clothes with a mixture of hot water and lime 10% for 10 minutes to reduce the number of bacteria Staphylococcus aureus in used clothing, the results of this study are expected to be an alternative to reduce the amount of bacteria Staphylococcus aureus in used clothing, and further research needs to be done using a solution of lime juice in decreasing the number of other pathogenic bacteria found in used clothing. Keywords: Lime juice, hot water, Staphylococcus aureus